2015
DOI: 10.1128/aac.04221-14
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Spondylitis in Russia and Prominent Role of Multidrug-Resistant Clone Mycobacterium tuberculosis Beijing B0/W148

Abstract: Extrapulmonary and, in particular, spinal tuberculosis (TB) constitutes a minor but significant part of the total TB incidence. In spite of this, almost no studies on the genetic diversity and drug resistance of Mycobacterium tuberculosis isolates from spinal TB patients have been published to date. Here, we report results of the first Russian and globally largest molecular study of M. tuberculosis isolates recovered from patients with tuberculous spondylitis (TBS). The majority of 107 isolates were assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
1
23
1
5
Order By: Relevance
“…Vyazovaya's research was showed mutations in rpoB531 were most commonly found among Beijing isolates (60 of 72 isolates with rpoB mutations), five isolates (four of which were Beijing) were showed multiple or triple mutations in rpoB. INH resistance mutations, the katG315 mutation is also the most common in Beijing isolates 30 . Studies from Estonia, China, Korea and Taiwan were showed a significantly higher MDR frequency among Beijing descendants 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Vyazovaya's research was showed mutations in rpoB531 were most commonly found among Beijing isolates (60 of 72 isolates with rpoB mutations), five isolates (four of which were Beijing) were showed multiple or triple mutations in rpoB. INH resistance mutations, the katG315 mutation is also the most common in Beijing isolates 30 . Studies from Estonia, China, Korea and Taiwan were showed a significantly higher MDR frequency among Beijing descendants 31 .…”
Section: Discussionmentioning
confidence: 97%
“…у ранее леченных больных ту-беркулезом легких [1]. При этом ранее доказана клиническая значимость и преимущественно эпидемический путь распространения МЛУ штаммов M. tuberculosis генотипа Beijing на тер-ритории России [2,4,6,12,15]. Штаммы дан-ного генотипа характеризует наличие, по мень-шей мере, трех спейсеров 35-43 и отсутствие 1-34 спейсеров в профиле сполиготипирова-ния (табл.…”
Section: Discussionunclassified
“…Нами впервые показано, что среди штаммов M. tuberculosis, выделенных от больных хрони-ческим туберкулезом легких в Ленинградской области, также превалируют представители генетического семейства Beijing, причем их доля возросла с 56, [3,6,9,11,15].…”
Section: Discussionunclassified
“…Nevertheless, some common and distinctive observations can be made based on recent genotyping studies on EPTB in different countries. For example, in Russia, a study of spinal TB (TBS) found that 75% of strains were of the Beijing type, a proportion greater than that of the national prevalence of pure PTBs (50). More-over, 95% of these Beijing TBS were multidrug resistant, bearing mutations katG315 and rpoB531 commonly found in PTBs.…”
Section: Discussionmentioning
confidence: 99%